Surgical outcomes of thoracic endovascular aortic repair for retrograde Stanford type a dissection. (27th February 2023) - Koizumi, Shigeki; Inoue, Yosuke; Shinzato, Kento; Yokawa, Koki; Kasai, Mio; Masada, Kenta; Seike, Yoshimasa; Sasaki, Hiroaki; Matsuda, Hitoshi
Abstract: OBJECTIVES: The optimal indications and contraindications for thoracic endovascular aortic repair of retrograde Stanford type A acute aortic dissection (R-AAAD) are not well known. The goal of this study was to determine the outcomes of thoracic endovascular aortic repair for R-AAAD at our institution and to discuss optimal indications. METHODS: The medical records of 359 patients admitted to our institution for R-AAAD between December 2016 and December 2022 were reviewed, and 83 patients were finally diagnosed with R-AAAD. We selected thoracic endovascular aortic repair as an alternative, considering the anatomy of aortic dissection and the risk to patients undergoing open surgery. RESULTS: Nineteen patients underwent thoracic endovascular aortic repair for R-AAAD. No in-hospital deaths or neurologic complications occurred. A type Ia endoleak was detected in 1 patient. All other primary entries were successfully closed. All dissection-related complications, such as cardiac tamponade, malperfusion distal to the primary entry and abdominal aortic rupture, were resolved. One patient required open conversion for intimal injury at the proximal edge of the stent graft; all other ascending false lumens were completely thrombosed and contracted at discharge. During the follow-up period, no aortic-related deaths or aortic events proximal to the stent graft occurred. CONCLUSIONS: The indications for thoracic endovascular aortic repair were expanded to low-risk and emergency cases at our institution. The early- and midterm outcomes of thoracic endovascular aortic repair for R-AAAD were acceptable. Further long-term follow-up is required. Abstract : Stanford acute type A aortic dissection (AAAD) is a life-threatening aortic emergency and often requires surgical treatment.